Nursing students' academic self‐efficacy: A longitudinal analysis of academic self‐efficacy changes and predictive variables over time. (9th February 2021) - Bulfone, Giampiera; Badolamenti, Sondra; Biagioli, Valentina; Maurici, Massimo; Macale, Loreana; Sili, Alessandro; Vellone, Ercole; Alvaro, Rosaria
Abstract: Aim: To analyse any changes seen in the academic self‐efficacy of nursing students during the three years of their academic education as well as the associated predictive factors. Design: A longitudinal study design was applied. Methods: The sample included 220 students who attended a large university in central Italy. The students' academic self‐efficacy was measured using the Academic Nurses' Self‐Efficacy Scale. Data were collected annually from 2014/2015 to 2017/2018 at the beginning of the first year (T0), at the end of the first year (T1), at the end of the second year (T2) and at the end of the third year (T3). A repeated measure univariate analysis of variance (ANOVA) was conducted to detect any possible changes in the students' academic self‐efficacy scores over the four measurement points. To identify the factors that are predictive of academic self‐efficacy, a linear regression model was used. Results: Overall, the students' academic self‐efficacy did not change significantly over the three‐year period of their education. Both sex (female) and age (24–50 years) during T0–T2 significantly predicted changes in the students' academic self‐efficacy over time. Moreover female students started with lower academic self‐efficacy scores than male students, although their academic self‐efficacy increased over time, while the male students' academic self‐efficacy actually decreased over time. In addition, students with a scientific background reported higher academic self‐efficacy than other students. Conclusions: Although the students' academic self‐efficacy did not change over time, from a theoretical perspective, academic self‐efficacy can be developed using a number of strategies such as a well‐organised tutorial during the clinical learning phase and feedback or encouragement. Impact: Academic staff should monitor nursing students' academic self‐efficacy over time, particularly in the case of male and younger students, students with a partner and students with a humanities background during the first 2 years of the course.